Information Integration, Coordination Failures, and Quality of Prescribing - Petri Böckerman; Liisa T. Laine; Mikko Nurminen; Tanja Saxell (Valtion taloudellinen tutkimuskeskus, 2022)
Poor information flows hamper coordination, potentially leading to suboptimal decisions in health care. We examine the effects of a nationwide policy of information integration on the quality of prescribing. We use the rollout of an electronic prescribing system in Finland and prescription-level administrative data. We find no effect on the probability of co-prescribing harmful drug combinations in urban regions. In rural regions, this probability reduces substantially, by 35 percent. The effect is driven by prescriptions from unspecialized physicians and from multiple physicians. Improving the local information environment thus enhances coordination and narrows differences in the quality of prescribing.